CO2 absorption into K2CO3/KHCO3 solution enhanced by organic phase in a rotor–stator reactor. Issue 7 (2nd May 2020) - Feng, Qi; Wang, Yanan; Wang, Lei; Zhao, Wei; Arowo, Moses; Shao, Lei
ABSTRACT: This work studied the gas–liquid–liquid (G–L–L) reaction system of CO2 absorption into K2 CO3 /KHCO3 buffer solution enhanced by organic phase in a rotor–stator reactor (RSR). The effects of volume fraction of organic phase, type of organic phase, rotational speed of RSR, gas and liquid volumetric flow rate, and temperature on CO2 absorption percentage were investigated. Results indicate that the addition of the organic phase with a volume fraction of 1.3–1.6% had significant promoting effect on CO2 absorption. CO2 absorption percentage increased with increase in the rotational speed of the RSR but decreased with rise in liquid temperature and gas–liquid ratio. This work demonstrates that RSR can significantly enhance liquid–liquid mixing and gas–liquid mass transfer processes in the G–L–L system.